Improving PAI Learning Outcomes Through Sharing Models and Audiovisual Media on Shu'abul Iman Material - Rizki Ardila (BiCED Proceeding, 2024)
This study aims to improve students' learning outcomes in the Shu'abul Iman competency through the application of the sharing learning model combined with audio-visual media. This classroom action research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observation sheets, and interviews. The findings revealed that the integration of the sharing model and audio-visual media significantly enhanced students' learning outcomes. In the first cycle, the mastery level reached 81.25%, which increased to 100% in the second cycle. This method also improved student engagement during the learning process, as evidenced by active participation in discussions and interactions. These results align with constructivist theory, multimedia learning, and active learning, emphasizing the importance of active student involvement and the use of relevant media to create meaningful learning experiences. Thus, implementing the sharing model and audio-visual media is effective in improving student learning outcomes while fostering a deeper understanding of Shu'abul Iman material.